2009
DOI: 10.1002/qua.560080714
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of the conformational properties of biological phenethylamines by molecular orbital techniques

Abstract: P c i L o computations using x-ray determined crystal geometry as input data indicate that the ytruche and ~I ' L I J I S conformers have practically identical energies in the majority of fundamental biological phenethylamines and phenethanolamines. Ah iriitio STO 3G computations indicate a small but definite preference of the isolated molecule for a guuche conformation. This result is confirmed for phenethylamine by an rib iriirio 4-31 G computation and by a computation using Clementi's 7s. 3pi3.s basis contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is pertinent to mention that, for quite some time now, theoretical studies have become essentially useful to gain a better understanding on the behavior of DA, even if some of the papers referred exhibited somewhat obsolete methods. The majority of the computational studies of DA that have been developed are related to its conformational properties in the gaseous phase 23-25 and also in the presence of solvent. ,, Some of the species that result from DA's deprotonation processes 25 have been studied. However, up to this moment, there is not a detailed study on the molecular structures of all the isomers resulting from proton losses (see Schemes −3) and their proton affinities which may become directly related to a set of properties derived from pH changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent to mention that, for quite some time now, theoretical studies have become essentially useful to gain a better understanding on the behavior of DA, even if some of the papers referred exhibited somewhat obsolete methods. The majority of the computational studies of DA that have been developed are related to its conformational properties in the gaseous phase 23-25 and also in the presence of solvent. ,, Some of the species that result from DA's deprotonation processes 25 have been studied. However, up to this moment, there is not a detailed study on the molecular structures of all the isomers resulting from proton losses (see Schemes −3) and their proton affinities which may become directly related to a set of properties derived from pH changes.…”
Section: Introductionmentioning
confidence: 99%
“…It is pertinent to mention that, for quite some time now, theoretical studies have become essentially useful to gain a better understanding on the behavior of DA, [18][19][20][21][22][23][24][25][26] even if some of the papers referred exhibited somewhat obsolete methods. [18][19][20][21] The majority of the computational studies of DA that have been developed are related to its conformational properties in the gaseous phase [23][24][25] and also in the presence of solvent. 23,25,26 Some of the species that result from DA's deprotonation processes 25 have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the increase in many diseases, such as irregular heartbeats, shortage of breath, and PD, that is happening not only among old people but also in young people is what motivates this study. As the band gap is the threshold for photons to be absorbed, determination of the variation of the band gap will give us a measure of effectiveness of dopamine for curing. Research in band gap control can provide a complete control in the activity of the title molecule in the reaction mechanism of the molecule in the human body. Free radicals and harmful chemical species in the human body always originate from aerobic metabolism and other processes, like smoking, use of pesticides, herbicides, and drugs, and ionization radiation. , All these process can change the balance of the oxidation–reduction reaction in the body, which leads to problems like hypertension, cancer, cardiovascular diseases, and neurodegenerative disorders such as PD and Huntington’s disease. That is why this research focuses on improving the efficiency of dopamine activity to produce molecules that will balance oxidants and anti-oxidants present in the body, which will be helpful for curing many detected and undetected diseases. Also, we investigated the behavior of doping of ascorbic acid with halogens and the effect of changes in the band gap when doping took place and concluded that the band gap of ascorbic acid responded to the introduction of halogen atoms based on their position in the electronegative series, thus increasing the effectiveness of ascorbic acid in radical scavenging in the human body …”
Section: Introductionmentioning
confidence: 99%
“… 28 − 34 Free radicals and harmful chemical species in the human body always originate from aerobic metabolism and other processes, like smoking, use of pesticides, herbicides, and drugs, and ionization radiation. 5 , 35 41 All these process can change the balance of the oxidation–reduction reaction in the body, which leads to problems like hypertension, cancer, cardiovascular diseases, and neurodegenerative disorders such as PD and Huntington’s disease. 42 45 That is why this research focuses on improving the efficiency of dopamine activity to produce molecules that will balance oxidants and anti-oxidants present in the body, which will be helpful for curing many detected and undetected diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the interactions of biologically interesting molecules, it is necessary to know the shape of the interaction sites as well as the conformations of the interacting molecules and, the conformational analysis of Ach has been subject of many experimental 6–25 and theoretical 26–46 investigations. Aspects of the Ach potential energy surface (PES) have been the subject of numerous experimental investigations including X‐Ray 6–8, 16–21, NMR 9, 11–14, 23, 25, electron diffraction 22, and Raman Spectroscopy 15, in addition, computational studies have employed ab initio 3, 31, 34, 35, 42–44, semi empirical and empirical methods 26–30, 38, 39 as well as molecular dynamics 36, 37, 45.…”
Section: Introductionmentioning
confidence: 99%